2006
DOI: 10.1063/1.2197291
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ti in NaAlH4

Abstract: There has been confusion which external reference should be used for predicting ground state Ti substitution enthalpies in NaAlH4: element gaseous atomic states or standard states. It is proposed instead to use all the relevant product phases for the Ti-enhanced sodium alanate system as internal reference states. The results are similar to when external reference element standard states are used: Ti doping is unstable in NaAlH4, and substitution on the Al sublattice is the least unfavorable. Substitution near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 29 publications
4
48
0
Order By: Relevance
“…To calculate the potential effect of bulk substituted titanium on the hydrogen dynamics, the Al-sites were used since they are energetically preferred over Na-sites for both NaAlH 4 [25] and Na 3 AlH 6 [17]. For an insignificant fraction of the hydrogen atoms in doped Na 3 AlH 6 (< 1% for doping with 4 mol% TiCl 3 ), the activation energy for long range diffusion could be lowered to 0.36 eV (see Table 1).…”
Section: Calculations Resultsmentioning
confidence: 99%
“…To calculate the potential effect of bulk substituted titanium on the hydrogen dynamics, the Al-sites were used since they are energetically preferred over Na-sites for both NaAlH 4 [25] and Na 3 AlH 6 [17]. For an insignificant fraction of the hydrogen atoms in doped Na 3 AlH 6 (< 1% for doping with 4 mol% TiCl 3 ), the activation energy for long range diffusion could be lowered to 0.36 eV (see Table 1).…”
Section: Calculations Resultsmentioning
confidence: 99%
“…24 Contrarily, Løvvik and Opalka claim that Ti primarily moves to interfaces between Al and NaAlH 4 , grain boundaries, or to defects in the NaAlH 4 particles. 25 Alternatively, it is also reported that Ti on an Al surface might be the active Ti entity. [26][27][28] Geerlings et al showed that the rate of hydrogen reloading decreases with increasing temperature of the preceding hydrogen desorption step.…”
Section: Introductionmentioning
confidence: 99%
“…11 The correlation among the catalytic role, structure, and location of the Ti for (de)hydriding catalysis is not fully understood, although it has been the subject of many investigations in the past years. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] A H 2 /D 2 scrambling study performed by Schüth et al points out that the Ti after doping dissociates hydrogen at room temperature, suggesting that one of the roles of the Ti catalyst might be to split hydrogen. 12 Alternatively, it is suggested that Ti facilitates migration of H via interstitials 13 or facilitates migration of metal atoms in the form of AlH 3 units.…”
Section: Introductionmentioning
confidence: 99%
“…These results leave Ti in the Al phase as the only firmly established location, even though it is often hypothesized that Ti might be present on surfaces and at interfaces between the parent and product phases in Eqs. 1 and 2 (15).…”
mentioning
confidence: 99%